2012
DOI: 10.1108/17538351211215366
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of employee's dog presence on stress and organizational perceptions

Abstract: PurposeThe purpose of this paper is to present a preliminary study of the effect of the presence at work of employees' dogs on stress and organizational perceptions.Design/methodology/approachA pre‐post between‐group design with repeated measures was used to compare differences between employees who bring their dogs to work (DOG group), employees who do not bring their dogs to work (NODOG group), and employees without pets (NOPET group) on physiological and perceived stress, perceptions of job satisfaction, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Visual analog scales are widely used self-report measures with acceptable reliability and validity in assessing a wide range of health outcomes including pain (Ahles, Ruckdeschel and Blanchard 1984), anxiety (Barker, Pandurangi and Best 2003), feelings (Aitken 1969), and mood (Ahearn 1997). The same SVAS has previously been used in assessing the effect of canine-assisted therapy on stress in healthy adults (Barker et al 2010;Barker et al 2012) and college students (Barker, Barker, and Schubert 2014). The authors have used similar scales to assess the effect of animal-assisted activities on anxiety, depression, and fear, with significant test-retest correlations (r = 0.79, p < 0.001) for anxiety, and concurrent validity supported by significant correlations (r = 0.68, p = 0.005) between patient-nurse ratings (Barker et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Visual analog scales are widely used self-report measures with acceptable reliability and validity in assessing a wide range of health outcomes including pain (Ahles, Ruckdeschel and Blanchard 1984), anxiety (Barker, Pandurangi and Best 2003), feelings (Aitken 1969), and mood (Ahearn 1997). The same SVAS has previously been used in assessing the effect of canine-assisted therapy on stress in healthy adults (Barker et al 2010;Barker et al 2012) and college students (Barker, Barker, and Schubert 2014). The authors have used similar scales to assess the effect of animal-assisted activities on anxiety, depression, and fear, with significant test-retest correlations (r = 0.79, p < 0.001) for anxiety, and concurrent validity supported by significant correlations (r = 0.68, p = 0.005) between patient-nurse ratings (Barker et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of dogs in the workplace has been identified as a low-cost wellness intervention in the workplace [4] which Wells & Perrine [62] found to help reduce the perception of stress and lead to secondary benefits such as improved health and organizational satisfaction (as cited in 4). Recent experimental research [4] found that, when compared to controls, employees who brought their dogs to work experienced reduced stress throughout the workday. Furthermore, nearly half of the employees who brought their dog to work reported their dog to be either very important or somewhat important to their productivity.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, nearly half of the employees who brought their dog to work reported their dog to be either very important or somewhat important to their productivity. These researchers speculate that unique dog-related communication may have led to improved employee perceptions of job satisfaction: anecdotes of mail deliveries made by employees with their dogs, members of management visiting employee areas with their dogs, and self-reported improvements to employee morale [4] are indicative of the benefits of dogs in the workplace for all stakeholders.…”
Section: Methodsmentioning
confidence: 99%
“…4 Of course, even where first-line managers are not providing reflective supervision, this does not mean they are failing to support their workers. On the contrary, 3 At least, not since they were students. 4 According to a recent Department for Education estimate, the average social work caseload in England is 16.1, a figure that was roundly derided by practitioners on twitter and elsewhere (McNicoll, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are many large organisations in the world and most do not address problems of stress and retention by providing reflective supervision. priorities for a future research agenda, one of which was developing an evidence base for the 1 Bringing dogs into the workplace as a method to reduce stress seems a remarkably well-evidenced intervention (Barker et al, 2012). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 suggesting that the provision of professional supervision in contemporary Australian contexts at least is exceptionally challenging (Egan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%